The innovators : how a group of inventors, hackers, geniuses, and geeks created the digital revolution - Isaacson, Walter (New York : Simon & Schuster, 2014)
The Innovators is Walter Isaacson's revealing story of the people who created the computer and the Internet. It is also a history of the digital revolution and a guide to how innovation really happens. What were the talents that allowed certain inventors and entrepreneurs to turn their visionary ideas into disruptive realities? What led to their creative leaps? Why did some succeed and others fail? Isaacson begins with Ada Lovelace, Lord Byron's daughter, who pioneered computer programming in the 1840s. He explores the fascinating personalities that cr eated our current digital revolution, such as Vannevar Bush, Alan Turing, John von Neumann, J.C.R. Licklider, Doug Engelbart, Robert Noyce, Bill Gates, Steve Wozniak, Steve Jobs, Tim Berners-Lee, and Larry Page. This is the story of how their minds worked and what made them so inventive. It's also a narrative of how their ability to collaborate and master the art of teamwork made them even more creative. For an era that seeks to foster innovation, creativity, and teamwork, The Innovators shows how they happen.
Ada, Countess of Lovelace -- The computer -- Programming -- The transistor -- The microchip -- Video games -- The Internet -- The personal computer -- Software -- Online -- The Web -- Ada forever.
Includes bibliographical references (pages 493-523) and index.
Keywords: Lovelace, Ada King, -- Countess of, -- 1815-1852.; Babbage, Charles, -- 1791-1871.; Bush, Vannevar, -- 1890-1974.; Eckert, J. Presper -- 1919-1995.; Licklider, J. C. R; Mauchly, John W. -- 1907-1980.; Noyce, Robert N. -- 1927-1990.; Roberts, L. G; Shockley, William, -- 1910-1989.; Taylor, R. W. -- 1932-; Von Neumann, John, -- 1903-1957.; Bell Telephone Laboratories; Computer scientists -- Biography; Computer science -- History; Internet -- History; Creative ability in technology; BIOGRAPHY & AUTOBIOGRAPHY / Science & Technology; BUSINESS & ECONOMICS / Industries / Computer Industry; TECHNOLOGY & ENGINEERING / History; Computer science; Computer scientists; Internet; Informatiker; Internet; Informatik; Biography; History